KEADILAN DAN PERLINDUNGAN HUKUM BAGI TENAGA KESEHATAN DALAM PERSPEKTIF FILSAFAT HUKUM: ANALISIS BERDASARKAN TEORI KEADILAN JOHN RAWLS DI INDONESIA - Asep Sapsudin; Chandra Chandra; Muhammad Sundari; Fifi Noviana (Bajang Institute, 2026)
Legal protection for healthcare workers is a fundamental aspect in ensuring fair and safe healthcare services. In practice, healthcare workers still face various risks, including violence, legal claims, and uncertainty in the application of legal norms. This study aims to analyze legal protection for healthcare workers in Indonesia and examine it from a legal philosophy perspective using John Rawls’ theory of justice. This research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that although legal regulations concerning healthcare worker protection exist, their implementation has not fully reflected substantive justice. Based on Rawls’ theory, this condition demonstrates that the principles of equal basic liberties and the difference principle have not been optimally fulfilled. Therefore, strengthening legal regulations and consistent law enforcement are necessary to create a more just protection system for healthcare workers.